2019
DOI: 10.1371/journal.pone.0216255
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on trimodal therapy versus radical cystectomy for muscle-invasive bladder cancer: Does the current quality of evidence justify definitive conclusions?

Abstract: Objectives To systematically review and meta-analyze the current literature in a methodologically rigorous and transparent manner for quantitative evidence on survival outcomes among patients diagnosed with muscle-invasive bladder cancer that were treated by either trimodal therapy or radical cystectomy. Materials and methods MEDLINE, EMBASE, CENTRAL were systematically searched for comparative observational studies reporting disease-specific survival and/or overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
(51 reference statements)
0
10
0
1
Order By: Relevance
“…A study by Kulkarni et al [17] that included cisplatin-based TMT with definitive dosages showed results similar to ours, albeit with a smaller cohort from a single institution. Systematic reviews have shown that the published studies comparing TMT and RC are observational and at a high risk of bias [18] , [19] . The mixed picture presented by these nonrandomized studies cannot be the basis for an assessment of superiority of treatment modalities, but rather supports a balanced discussion with patients of two treatment approaches with comparable outcomes in appropriately selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kulkarni et al [17] that included cisplatin-based TMT with definitive dosages showed results similar to ours, albeit with a smaller cohort from a single institution. Systematic reviews have shown that the published studies comparing TMT and RC are observational and at a high risk of bias [18] , [19] . The mixed picture presented by these nonrandomized studies cannot be the basis for an assessment of superiority of treatment modalities, but rather supports a balanced discussion with patients of two treatment approaches with comparable outcomes in appropriately selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in these patients, trimodal therapy consisting of either transurethral resection or partial cystectomy followed by radiotherapy with concurrent chemotherapy is currently considered to yield the best oncologic outcomes [ 4 , 65 ]. Although the trimodal therapy may increase quality-adjusted life years, current data on overall survival or disease-specific survival are still in favor of radical cystectomy [ 82 ]. Thus, the development of the novel radiosensitization strategies is required to replace radical cystectomy with radiotherapy as a gold standard option for some MI bladder cancers.…”
Section: Sex Hormone Receptor Signaling and Sensitivity To Conventional Non-surgical Treatment For Bladder Cancermentioning
confidence: 99%
“…Trimodal therapy consisting of either transurethral resection of the bladder or partial cystectomy followed by radiotherapy with concurrent chemotherapy is currently considered to yield the best oncologic outcomes in select patients with muscle-invasive BCa. A recent metaanalysis demonstrated the findings in favor of radical cystectomy, with hazard ratios (95% confidence interval [CI]) of 1.39 (1.03-1.88) and 1.39 (1.20-1.59) for disease-specific survival (DSS) and overall survival (OS), respectively [6]. However, trimodal therapy in appropriately selected patients has been suggested to increase quality-adjusted life years, compared with radical cystectomy.…”
Section: Trimodal Therapymentioning
confidence: 99%